Studies on Canal Water Based Pressurized Irrigation System in a Minor Irrigation Command - Srivastava, R C; Mohanty, S; Singandhupe, R B; Biswal, A K; Ray, L.I.P; Sahoo, D (Journal of Agricultural Engineering, 2006)
The flow based minor irrigation systems are common in the plateau areas of eastern India. However due to rolling topography and coarse soil texture, the irrigation efficiency is quite poor. With rolling topography, a scope exists to shift from surface irrigation to hybrid application system comprising gravity fed pipe conveyance and surface irrigation for rice in monsoon season and pumped pressurized irrigation system for post-monsoon crops. A system comprising an adjunct reservoir, a common mainline with option of sprinkler and drip at desirable location was designed for one outlet of a minor irrigation system and was evaluated for its hydraulics and irrigation efficiency. The system reduced the turbidity of the canal water from 11-16 NTU to 2-3 NTU in three stages i.e. adjunct reservoir, catchwell and filtration unit. It was found that the irrigation efficiency of sprinkler and drip irrigation systems were 77.2% and 90.19% respectively in comparison to 46.14% in case of surface irrigation system. The uniformity coefficients of sprinkler irrigation system and emission uniformity of drip irrigation system were 81.4% and 94.2% respectively. Thus the above system can be successfully used in minor irrigation commands, for increasing irrigation efficiency as well as yields. The economic analysis of the system indicated that if the cost of hybrid drip and sprinkler irrigation system is less than Rs. 38,000.00 /ha, then saving water through this system will be more economical.